2006
DOI: 10.1111/j.1582-4934.2006.tb00415.x
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9 and MMP-2 gelatinases and TIMP-1 and TIMP-2 inhibitors in breast cancer: correlations with prognostic factors

Abstract: The matrix metalloproteinases (MMPs) are a family of structurally and functionally related proteinases, initially characterized by their ability to degrade the extracellular matrix (ECM) [1]. Nowadays, at least 20 enzymes that share considerable homology within their major domains (signal peptide, propeptide, catalytic, hinge and hemopexin-like domains) were included in MMPs family [2]. Most of MMPs are synthesised and secreted as partially activated latent forms, requiring, for full activation, removal of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 54 publications
5
102
0
4
Order By: Relevance
“…Kadoglou et al (24) demonstrated that exercise reduces MMP-9 serum levels, but not MMP-2 levels, in patients with type 2 diabetes. Additional studies have investigated the function of circulating MMP-2 and MMP-9 in BC patients (51,52); the results revealed increased MMP-9 expression and activity in malignant tumors, and enhanced MMP-2 activity in malignant tumors exhibiting high estrogen receptor expression. These studies indicate that serum levels of MMP-2 or -9 may present useful markers for the staging and prognosis of BC and other types of cancer (53), such as prostate adenocarcinoma, in association with prostate-specific antigen levels, gastric cancer and lung carcinoma (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Kadoglou et al (24) demonstrated that exercise reduces MMP-9 serum levels, but not MMP-2 levels, in patients with type 2 diabetes. Additional studies have investigated the function of circulating MMP-2 and MMP-9 in BC patients (51,52); the results revealed increased MMP-9 expression and activity in malignant tumors, and enhanced MMP-2 activity in malignant tumors exhibiting high estrogen receptor expression. These studies indicate that serum levels of MMP-2 or -9 may present useful markers for the staging and prognosis of BC and other types of cancer (53), such as prostate adenocarcinoma, in association with prostate-specific antigen levels, gastric cancer and lung carcinoma (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…The stromal desmoplastic response is characterized by the activation of fibroblasts, increased deposition, cross-linking and remodeling of the ECM, angiogenesis, and invasion of leukocytes. Up-regulated ECM gene expression and elevated MMP activities are not only found in tumors but can also correlate with poor patient prognosis (Jinga et al, 2006). For example, expression levels of the ECM protein lysyl oxidase (LOX), which is responsible for collagen cross-linking, is elevated in cancer patients and associated with metastasis and reduced patient survival (Erler et al, 2006).…”
Section: Associated Pathologiesmentioning
confidence: 99%
“…For example, expression levels of the ECM protein lysyl oxidase (LOX), which is responsible for collagen cross-linking, is elevated in cancer patients and associated with metastasis and reduced patient survival (Erler et al, 2006). Furthermore, the increased ratios of MMP2:TIMP2 and MMP9:TIMP1 found in malignant breast tissues have been suggested to play a role in the aggressiveness of invasive breast carcinomas (Jinga et al, 2006).…”
Section: Associated Pathologiesmentioning
confidence: 99%
“…MMP-2 is a protein associated with metastasis and is extensively studied in several cancers. [11][12][13][14][15][16] ER and MMP-2 have shown a molecular relationship with E2 or estradiol binding in the E domains of ER, present in the plasma membrane. This interaction could activate MMP-2 and MMP-9 with subsequent transactivation of EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…A loss of control of MMPs can result in pathological processes including inflammation, angiogenesis, cellular proliferation 11,12 and are directly involved in the metastatic tumor cell invasion process. 9 Among them, gelatinase A (MMP-2) is associated with a malignant phenotype, as it is responsible for the degradation of collagen fibers around tumors, thereby releasing these cells from the microenvironment in which they are established.…”
Section: Introductionmentioning
confidence: 99%